Looking into the Future: the Spread and Realization of Guerrilla Warfare Tactics in Lithuania in 1944–1953 - Jokubauskas, Vytautas (Genocidas ir rezistencija, 2011)
The post-war guerrilla warfare in Lithuania was nothing new since the traditions of the guerrilla movement dated back to the 1919–1923 battles for independence and confrontations with Polish forces in the neutral territory. In the interwar period, the Lithuanian military authorities did not discard guerrilla warfare tactics, and this form of warfare was essentially legitimised by the Hague Convention on Warfare of 1907. In 1935, upon the militarisation of the Lithuanian Riflemen’s Union and its integration in the regular army structures, the training of riflemen for the eventual occupation of the country’s territory by the enemy was rather intensive. The ideas of partisan warfare were promoted by means of the periodical Trimitas (The Trumpet) and incorporated in the documents of the General Staff, which provided for the action of partisans in small units on well-known territory by using light armament and setting the objective of continuous assaults on the enemy, thereby demoralising him. In 1940, following the Soviet occupation and liquidation of the Lithuanian Riflemen’s Union, the structure, after its development for two decades, remained, and the personal contacts of riflemen were quite intensive. A network of riflemen units, the locally operating unit serving as the main tactical and administrative entity of the union, covered the entire territory of Lithuania and was a suitable basis for the organisation of post-war guerrilla warfare, while the former riflemen and officers acted as organisers and leaders of the resistance movement. The above facts allow us to conclude that the guerrilla warfare waged against the Soviet forces of repressions and military units in Lithuania in 1944 to 1953 was influenced by pre-war Lithuanian military plans, while the warfare itself was a legitimate defence of the nation’s sovereignty with respect to international military law and should be regarded as pre-planned resistance to eventual occupation.